2017
DOI: 10.1016/j.celrep.2017.04.052
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Interleukin-13 at Pancreatic ADM/PanIN Lesions Alters Macrophage Populations and Mediates Pancreatic Tumorigenesis

Abstract: SUMMARY The contributions of the innate immune system to the development of pancreatic cancer are still ill-defined. Inflammatory macrophages can initiate metaplasia of pancreatic acinar cells to a duct-like phenotype (ADM), which then give rise to pancreatic intraepithelial neoplasia (PanIN) when oncogenic KRas is present. However, it remains unclear when and how this inflammatory macrophage population is replaced by tumor-promoting macrophages. We here demonstrate presence of interleukin-13 (IL-13), which ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
116
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(131 citation statements)
references
References 36 publications
5
116
0
1
Order By: Relevance
“…Recently, in a KRAS model of PDA, tumor-associated macrophages increased with ductal metaplasia and neoplastic transformation, effects that appeared to depend on IL-13 released from cancer cells. 47 On the other hand, several pathways have been proposed to mediate the effects of tumor-associated macrophages on cancerous epithelium. 10,13,29 Here we found that expression of PEDF, a tumor suppressor in PDA, decreases in the transforming epithelium not due to KRAS mutation but upon exposure to macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a KRAS model of PDA, tumor-associated macrophages increased with ductal metaplasia and neoplastic transformation, effects that appeared to depend on IL-13 released from cancer cells. 47 On the other hand, several pathways have been proposed to mediate the effects of tumor-associated macrophages on cancerous epithelium. 10,13,29 Here we found that expression of PEDF, a tumor suppressor in PDA, decreases in the transforming epithelium not due to KRAS mutation but upon exposure to macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Enrichment of DCLK1 and acetylated α-tubulin in the FACS-sorted CD133 + population of PDAC cells was reported (Bailey et al, 2014). Expression of CD133, DCLK1 and CD44 were present in PanIN cells of oncogenic Kras G12D mouse pancreas (Fig 2, (Bailey et al, 2014, Delgiorno et al, 2014, Liou et al, 2017)). However, these 3 CSC markers were expressed in different subpopulations of murine PanIN cells (Fig 2.…”
Section: Cd133 In Cancer Development and Progressionmentioning
confidence: 91%
“…Macrophage-secreted inflammatory cytokines, such as tumour necrosis factor (TNF) and CC motif chemokine 5 (CCL5), play roles in pancreatic ADM, with contributions from macrophage-released matrix metalloproteinases (MMPs), such as MMP9, as well 131,132 . Recently, it was demonstrated that IL-13 alters macrophage populations from an inflammatory macrophage subpopulation to an alternatively activated macrophage subpopulation in ADM 133 . The development of Barrett-like metaplasia in the mouse requires the suppression of CD8 + T cell-dependent apoptosis of epithelial cells, which is probably mediated by CD11b + GR1 + immature myeloid cells or myeloid-derived suppressor cells 134 .…”
Section: Epigenetic and Genomic Considerationsmentioning
confidence: 99%